Physical And Sensory Disabilities: Legal Certainty And Justice In The Notary Profession - Tiara Maharani; M. Hamidi Masykur; Arini Jauharoh (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
This study examines the legal issues regarding the requirements for appointment as a Notary as regulated in Article 3 of the Notary Law (UUJN), with a focus on the regulation of physical and sensory disabilities. The background of this study is the incompleteness of norms in the UUJN which has the potential to cause legal uncertainty and discriminatory practices against persons with disabilities, both at the stage of appointing a Notary and against Notaries who experience life events that cause physical and/or sensory disabilities. The UUJN requires Notaries to be physically and mentally healthy, but does not provide explicit regulations regarding the limits and parameters of such health in relation to disabilities. This study aims to analyze the concept of physical and sensory disabilities in relation to the implementation of the Notary's authority and obligations and to formulate an ideal form of regulation to realize legal certainty and justice for all citizens. The research method used is normative legal research with a statutory approach and a conceptual approach. The analysis is carried out systematically and grammatically against the UUJN, the Health Law, the Law on Persons with Disabilities, and the Human Rights Law, and is based on the theory of legal certainty and dignified justice. The research results indicate that the requirement for physical health must be interpreted functionally, focusing on a person's ability to perform the duties of a notary, rather than on absolute physical condition. An analysis of the notary's authority and obligations indicates that upper locomotor and sensory functions play an essential role, while lower locomotor functions are not decisive. Therefore, this study proposes amendments to Article 3 of the UUJN by adding norms that recognize the ability to perform the position with or without reasonable accommodation, including the use of assistive technology. Furthermore, it is necessary to regulate leave procedures, functional assessments, and evaluations for notaries who experience disabilities after being appointed.